Community Resilience in Facing Fire Risk Case Study: RW 08, Penggilingan Village, Cakung District - Anastasia Chandra Lalita Meliala; Ayomi Dita Rarasati; Antony Sihombing (Politeknik Siber Cerdika Internasional, 2026)
Background: The concept of urban spatial planning should become the foundation for urban development and growth, as it determines the arrangement of communities, activities, buildings, infrastructure, and resources within a region. However, the aspect of fire disaster risk is often overlooked in residential area planning. In East Jakarta, particularly in Penggilingan Village, which has a high population density, the risk of fire disasters is considerably high. Objective: This study aims to examine community resilience through aspects of social resilience, economic resilience, and infrastructure and utility resilience. Methods: This study employed a convergent mixed-methods design. A total of 374 household heads (10% of 3,736 households across 15 RTs) were selected using proportional random sampling, while RT heads and officials from the East Jakarta Fire and Rescue Department (Gulkarmat) were recruited through purposive sampling. Data were collected through questionnaires and in-depth interviews, then analyzed using SPSS descriptive statistics and Miles and Huberman's thematic analysis. Results: Most RTs exhibited low social resilience, whereas economic and infrastructure-utility resilience were generally moderate. Low social resilience was mainly associated with limited community knowledge and fire preparedness, while inadequate hydrants and road access under 2 m reduced infrastructure resilience. Overall, community resilience was predominantly moderate (7 RT; 46.67%), followed by low (6 RT; 40.00%) and high (2 RT; 13.33%). Conclusion: Community resilience to fire disasters in RW 08 is generally moderate but requires further improvement. Strengthening hydrant availability, road accessibility, and community fire-preparedness programs should be prioritized to enhance resilience in densely populated neighborhoods across East Jakarta.